Cadre Capabilities In Preparation For Prevention Of Infective Diseases When Flood Disaster: Health Promotion Through Support Group - Rina Nur Hidayati; Arief Andriyanto; Faisal Ibnu (Alta Dharma Publisher, 2020)
Natural disasters that have both physical and psychological impacts are floods caused by human behavior. Disaster events caused by humans are things that need to be considered for immediate attention because it will cause some infectious diseases. Infectious diseases resulting from floods can be avoided by prevention activities that involve health cadres to take an active role in dealing with the problem of infectious diseases when floods occur. The study aimed to explore cadres’ ability in communicable disease preparedness when flood disasters through support groups. A quasi-experimental study, one group pre-test, and post-test without a control group was applied in this study. Forty-three samples were involved in this study from Gebangmalang Village, Mojoanyar District, Mojokerto Regency. Inclusion criteria; 1) cadres who are willing to become respondents; 2) cadres living in the study area; 3) cadres present at the intervention. 1-month research time. The results of the research show that the mean of knowledge, attitudes, and skills before and after the intervention increased from 34.9% to 100% good, 46.5% to 100% positive, and 55.8% to 100% good. Cadres increased the infectious diseases controlling when the flood disaster occurred with a p-value of 0.001. Increasing the ability of cadres was due to the interrelatedness between the knowledge, attitudes, and skills of a cadre. Based on the findings, community of nurses should provide to be able to prepare activities before a disaster occurs to be able to minimize the impact that occurs as a result of a disaster